Molecular Engineering of Enamine‐Based Hole‐Transporting Materials for High‐Performing Perovskite Solar Cells: Influence of the Central Heteroatom. Issue 11 (8th September 2022) - Vaitukaityte, Deimante; Truong, Minh Anh; Rakstys, Kasparas; Murdey, Richard; Funasaki, Tsukasa; Yamada, Takumi; Kanemitsu, Yoshihiko; Jankauskas, Vygintas; Getautis, Vytautas; Wakamiya, Atsushi
Abstract : Stabilizing the high‐performing perovskite solar cells (PSCs) with low‐cost and simply affordable hole‐transporting materials (HTMs) has been identified as an ongoing ambitious challenge. Herein, a series of enamine‐based HTMs having different central heteroatoms (C, N, O, and S) and a number of enamine branches is designed and synthesized. The impact of varied central heteroatom cores is investigated in‐depth including thermal, photophysical, and photovoltaic properties. Importantly, molecularly engineered HTMs are obtained by a single condensation reaction without the need for expensive catalysts, inert reaction conditions, or tedious product purification. PSCs with a power conversion efficiency (PCE) of over 20% can be realized with the triphenylamine core HTM (V1435), a result comparable with spiro‐OMeTAD. HTMs based on tetraphenylmethane (V1431) and diphenyl sulfide (V1434) cores give a slightly lower performance under similar device fabrication conditions. This work demonstrates how rational molecular engineering of a simple condensation approach can produce HTMs for high‐performing PSCs without sacrificing the PCE. Abstract : Engineering of the central heteroatom in the chemical structure of enamine hole‐transporting materials is presented, leading to the one‐pot‐synthesized low‐cost hole‐transporting material V1435 based on a nitrogen‐containing triphenylamine central core to reach a power conversion efficiency of over 20% in perovskite solar cells, which is on par with reference spiro‐OMeTAD.